Storeroom Management Module (SMM) development for ARCA web-based system / Nurshahira Yasmin Mohd Tarmizi ... [ et al.] - Mohd Tarmizi, Nurshahira Yasmin; Jamaluddin, Muhammad Nabil Fikri; Ibrahim, Alif Faisal; Mohd Fuzi, Mohd Faris; Jamil, Mohd Hairul Nazreen (Universiti Teknologi MARA, Perlis, 2022)
Storeroom is the most important storage area and it must be kept secured as it will be used by college students to keep their goods during semester break. They need to clear up the room before leaving the campus. To impose the security measure of storeroom, college management unit require students that are using the storeroom to write details and particulars before checking in and out the storeroom. This paper presents a development of Storeroom Management Module (SMM) for integration with Attendance Record for College Activities (ARCA) system. The module offers easy process when college staffs and students are dealing with storeroom. Module development involved three main phases which are feasibility study, design and development and module testing. Four components that comprises 17 questionnaires were included in technology acceptance model for module testing. Out of four components tested, component perceived user satisfaction (PUS) had received the highest mean score. This indicated that the developed SMM satisfied users in dealing with storeroom management module.